Frontispiece: Small‐Molecule Kinase‐Inhibitors‐Loaded Boron Cluster as Hybrid Agents for Glioma‐Cell‐Targeting Therapy. Issue 39 (12th July 2017) - Couto, Marcos; Mastandrea, Ignacio; Cabrera, Mauricio; Cabral, Pablo; Teixidor, Francesc; Cerecetto, Hugo; Viñas, Clara
Abstract : Hybrid anilinoquinazoline‐icosahedral boranes with anti‐glioma activity have been developed. It is is proposed that once the compound reaches the malignant cell, the presence of some transmembrane tyrosine kinase receptors, overproduced by unhealthy cell, provokes its accumulation in the tissue enriching with boron for further BNCT. Both structural motifs, anilinoquinazolinyl and icosahedral boron clusters, are connected using 1, 3‐dipolar cycloaddition or Sonogashira cross‐coupling processes. For more information, see the Communication by Clara Viñas et al. onpage 9233 ff.